Unlearning Gender - Kiss, Boglárka (Hungarian Journal of English and American Studies, 2021)
Book review: Repo, Jemima. The Biopolitics of Gender. Oxford: OUP, 2016. 218 pages. ISBN 978-0-19-025691-3. Hbk. Npr.